Kajian faktor risiko penyakit pulmonari tuberkulosis di Hospital Kuala Lumpur - Azmiza, M.; Choo, T.O; Haziah, M.; Ismail Tan; M.T.; Lim, Y.H.; Mohd Halmi; M.S.; Paul; N.A.; Rozaimah (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1998)
A case control study on pulmonary tuberculosis was conducted to determine the relationship between risk factors such as smoking habit, alcohol consumption, BCG vaccination and imunocompromised status with the occurrence of pulmonary tuberculosis. A total of 156 cases of pulmonary tuberculosis patients were identified from admission records at all medical wards in Hospital Kuala Lumpur from 1st January to 31st Disember 1995. However, only 76 cases were retrieved from the medical records department, Hospital Kuala Lumpur. A total of 76 controls matched for age, sex and ethnic groups were chosen by random sampling from all medical wards in Hospital Kuala Lumpur. The majority of pulmonary tuberculosis cases were Malays (56.6%), Indians 22.4%, Chinese 19.7% and other ethnic groups 1.3%. Out of this, 47.4% were males and 52.6% females.The study shown that BCG immunisation confers a significant protective effect on pulmonary tuberculosis. There was no significant relationship between smoking habit, alcohol consumption and imunocompromised state with tuberculosis infections.